Chemical constituents of Abies fabri. (September 2015) - Li, Yong-Li; Gao, Yan-Xia; Jin, Hui-Zi; Shan, Lei; Chang, Wan-Lin; Yang, Xian-Wen; Zeng, Hua-Wu; Wang, Ning; Steinmetz, Andre; Zhang, Wei-Dong
Graphical abstract: Twelve previously unreported compounds and 80 known ones were isolated from Abies fabri . Their structures were elucidated mainly by spectroscopic methods. The absolute configurations of compounds1, 3, and7 were determined by Cu-Kα X-ray crystallographic analysis. One known compound, 23-hydroxy-3-oxolanosta-8, 24-dien-26, 23-olide, showed weak cytotoxic activity against A549 and THP-1 cells. Highlights: Isolation of 12 previously unknown and 80 known compounds. Structure elucidation achieved mainly by analysis of NMR spectroscopic data. Absolute structures of three of these 12 compounds were established by Cu-Kα X-ray crystallography. One previously known compound showed weak cytotoxic activity against A549 and THP-1 cells. Abstract: Systematic phytochemical investigations on Abies fabri resulted in the isolation of 94 compounds, consisting of 68 terpenoids, six lignans, seven flavonoids, and 13 other miscellaneous chemical constituents. Their structures were elucidated on the basis of spectroscopic methods, and the absolute configurations of three of these previously unknown compounds were determined by Cu-Kα X-ray crystallographic analysis. Twelve previously unreported compounds, one artifact, and one potential artifact were identified, including six triterpenoids, four diterpenoids, two sesquiterpenoids, one lignan, and one phenol. 23-Hydroxy-3-oxolanosta-8, 24-dien-26, 23-olide showed weak cytotoxic activity against A549 and THP-1 cells with the IC50 values of 5.3 and 5.1 μM, respectively.